CHARACTER DEVELOPMENT OF THE MAIN CHARACTER IN JOKER MOVIE - Setiawan Negara, I Putu Gede (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
A character has a close relationship to personality and can be changed by the personality that the person has. The change of the character is determined by the conflict they have which leads to the development of the character. This study was aimed to analyze the psychological conflict and the influence of the main character in Joker Movie 2019. To understand the character of the Joker in the 2019 film, this study employed two key theories: Lewin's theory of psychological conflict and Hurlock's theory of character development. Researchers gathered data by analyzing the movie and its script, utilizing documentation and note-taking techniques. The analysis itself was qualitative, applying the aforementioned theories to interpret the Joker's transformation. The finding show Joker express two kinds of psychological conflict which are approach-avoidance conflict and avoidance-avoidance one. The approach-avoidance conflict insists Joker to choose two options when the conflict occurred, they are positive and negative. Meanwhile, the avoidance–avoidance conflict make Joker choose between negative and negative choices in Joker’s conflict. That two kinds of conflict influenced Arthur’s character development. There are four determinant which affect Arthur’s character development.  Physical determinant which was the appearance of Arthur made him being bullied, social determinant which Joker hard to interact with the others because of his mental illness, family determinant which Arthur realize he did not receive any love from his parents, and emotional determinant which Arthur realize his life was not a tragedy but comedy.